⁠Impact of Cigarette Smoking on Respiratory, Neurological and Dermatological Disorders: A Hospital-Based Study - Shoaib Saleem Khan, Kashif Sardar, Ubaid Ullah Ansari, Nighat Fatima, Zahid Habib Qureshi, Bakhtawar Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cigarette smoking is one of the largest preventable risk factors for morbidity at a systemic level. While the effects of smoking on the respiratory system are known, smoking may also cause neurological and dermatological disease via inflammation, oxidative stress, vascular dysfunction and impaired tissue oxygenation. Aims: This study was carried out to evaluate the effect of smoking on respiratory, neurological and dermatological diseases in adults in a clinical hospital setting. Methods: This hospital-based comparative cross-sectional study was conducted at Multan Medical and Dental College, Multan, from June 2022 to June 2023. One hundred twenty (120) adult subjects were recruited and split into two groups of equal size – 60 current cigarette smokers and 60 non-smokers. Demographic information, smoking history, number of cigarettes per day and pack-year exposure were documented. Patients were clinically evaluated for respiratory, neurological and dermatological manifestations in all. The data was analysed using SPSS version 26.0. Statistically significant difference between the groups was set at a p-value<0.05. Results: Among the smokers, the frequency of chronic cough, sputum production, wheezing, dyspnea on exertion, chronic bronchitis and recurrent respiratory infections were found to be significantly higher than the non-smokers. Smokers also had more neurological symptoms like headache, sleep disturbance, dizziness, memory complaints, and numbness or tingling. Smoking was significantly correlated with dermatological parameters like early wrinkles of the face, dryness of skin and delayed wound healing. Among smokers, those with > 10 pack-years had higher multisystem involvement. Conclusions: The respiratory, neurological and dermatological morbidity was significantly higher in the cigarette smoking group. Smoking status assessment and early smoking screening should be strengthened as routine practice in the hospital, along with smoking cessation counselling. Keywords: Cigarette smoking, respiratory disorders, neurological symptoms, dermatological disorders, hospital-based study